2022
DOI: 10.1101/2022.05.04.490631
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Adsorption of Pulmonary and Exogeneous Surfactants on SARS-CoV-2 Spike Protein

Abstract: COVID-19 is transmitted by inhaling SARS-CoV-2 virions, which are enveloped by a lipid bilayer decorated by a “crown” of Spike protein protrusions. In the respiratory tract, virions interact with surfactant films composed of phospholipids and cholesterol that coat lung airways. Here, we explore by using coarse-grained molecular dynamics simulations the physico-chemical mechanisms of surfactant adsorption on Spike proteins. With examples of zwitterionic dipalmitoyl phosphatidyl choline, cholesterol, and anionic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“… 11 13 Some of these studies have used jet-type nebulization, which is very ineffective owing to the use of air drags. 14 Nevertheless, other studies have demonstrated that the early use of postnatal nebulized surfactant may reduce the need for intubation in the first 3 days of life compared to nasal continuous positive airway pressure alone. 15 …”
Section: Discussionmentioning
confidence: 99%
“… 11 13 Some of these studies have used jet-type nebulization, which is very ineffective owing to the use of air drags. 14 Nevertheless, other studies have demonstrated that the early use of postnatal nebulized surfactant may reduce the need for intubation in the first 3 days of life compared to nasal continuous positive airway pressure alone. 15 …”
Section: Discussionmentioning
confidence: 99%